Synthesis and Carbonization of Core-Shell ZIF-67@ZIF-90 for Ciprofloxacin and Azithromycin Removal - Fatimah Al-Ghazzawi; Mohammed Mahdi Al-Mossawi; Amjad Al-Shawi; Kadhim Al-Attafi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The elimination of antibiotics such as Azithromycin (AZM) and Ciprofloxacin (CIP) from the contaminated water is crucial to safeguard both human health and environmental quality. This study investigates the synthesis of CoNC@NC core-shell composite by carbonizing ZIF-67@ZIF-90 composite, and the implementation of them in removing antibiotics from aqueous solutions. The composites were characterized using XRD, SEM, FTIR, Raman, TGA, and N2 adsorption-desorption. In the batch adsorption tests, the carbonized composite showed enhanced adsorption capacities compared to the original composite, with maximum adsorption capacities for AZM and CIP being 256.49 mg/g and 514.26 mg/g, respectively. The adsorption process was found to fit the pseudo-first-order kinetics and Langmuir isotherm models. The solution pH showed a significant impact on the adsorption capacity, with maximum capacities recorded at pH of 7 and 6 for the AZM and CIP solutions, respectively. In addition, it was demonstrated that after five regeneration cycles, the carbonized composite maintained the adsorption capacity at over 90% of the first cycle value, suggesting good reusability. These results revealed the potential of using CoNC@NC composites in environmental decontamination and antibiotic removal for wastewater treatment. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).